Stem cell 'therapy' advertisements in China: Infodemic, regulations and recommendations. (4th November 2020) - Lv, Jianwei; Su, Yeyang; Song, Lingqiao; Gong, Xia; Peng, Yaojin
Abstract: During the COVID‐19 pandemic, in addition to the pandemic itself, a phenomenon called an 'infodemic'—defined by the World Health Organization as the spread of misleading information on the pandemic—has also gained attention. In the field of stem cell research, researchers and regulators have been fighting against false and misleading information, particularly advertisements for unproven and unauthorized stem cell–based interventions for decades. However, how existing legal and regulatory measures, which vary by country, can be employed to combat such false information is unclear. In this article, we examine the situation in China, where the spread of unauthorized stem cell 'therapies' has drawn patients from not only within China but also from abroad. First, we assess how and to what extent online advertisements promote unproven and unauthorized stem cell–based interventions directly to patients and prospective health consumers in China. Next, we survey the landscape for existing regulatory and administrative measures that may be used to combat false and misleading advertisements in this area. Finally, based on our analysis, we provide three main recommendations that may improve the effectiveness and efficiency of the regulatory measures in curtailing illegitimate advertising of unproven and unauthorized stem cell–based interventions in China. In conclusion, we also call for international collaboration among researchers and regulators in studying and strengthening regulations in this critical area that has so far been neglected in scholarly and policy discussions.